New Insights into Re-3(mu-Cl)(3)Cl-6 Aromaticity. Evidence of sigma- and pi-Diatropicity - Vasquez-Espinal, A (2015)
It evaluated the behavior of the Re3(μ-Cl)3Cl6 cluster under magnetic perturbation, and it clearly shows that the magnetic response within the Re3(μ-Cl)3 plane is highly diatropic in nature. An analysis of both the magnetically induced current density (MICD) and induced magnetic field (Bind) allows us to classify this cluster as doubly σ- and also π-aromatic on the magnetic criterion. These findings contradict the classical Re–Re double bond representation and favor a chemical bonding pattern that involves delocalized bonds.